Application of ordered mesoporous SiO2 film for low power consumption in phase-change memory - Ha, Tae-Jung; Kim, Hyung Keun; Choi, Doo Jin; Shin, Sangwoo; Cho, Hyung Hee; Jang, Ho Won; Yoon, Seok-Jin; Park, Hyung-Ho (ELSEVIER, 2012)
This article presents an application of ordered mesoporous films to phase-change memory (PCM). Though ordered mesoporous SiO2 films have attracted attention due to their regular arrangement of nanometer-sized pores, they have not yet become an integral component in any application and have not been produced in a practical manner. Also, even though PCMs are potential next-generation memory devices, they have not made large market due to high power consumption, heat interference, and other shortcomings. In this work, ordered mesoporous SiO2 films were applied to an interlayer dielectric in PCM as a thermal insulating layer, resulting in one-quarter lower power consumption in PCM devices through the reduction of the power consumed in the RESET operation. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: THERMAL-CONDUCTIVITY; DIELECTRIC-CONSTANT; THIN-FILMS; STABILITY